A Review on Radiopharmaceuticals and Radiochemical Method in Analysis - Riddhi D, Patei (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Quality assurance is the sum of all parameters concerning the preparation and control of a finished product. It is a wide term commonly used for the confirmation and validity of various ways and measurements adopted to obtain a high quality procedure for intended use with guaranteed performance. Biological quality control of pharmaceutical products becomes essential as they are ultimately to be consumed by living organisms, in particular the humans. In thisreview, we have discussed the importance and significance of biological qualitycontrol in nuclear medicine. The current and new procedures for sterility, apyrogenecity and the biodistribution quality control have been discussed and evaluated in view of the future needs and modern trends in this important area of research. There are ionization chamber, scintillation and semi conductor detectors, liquid scintillation counter, Beta emitting radionuclide, Gamma emitting radionuclide methods used in radiopharmaceuticals.